Tourism and quality of life - Lopes, Maria Carlos (2019)
The tourism travel industry has achieved higher growth rates than growth in the global economy (WTTC, 2017). For this growth, the wellness tourism segment has contributed a lot. Over the years, we have witnessed a growing concern on the part of the individual in improving their quality of life, manifested, essentially, by the demand for spas and thermal resorts. Quality of life is a reality studied in several domains of society. Its definition and measurement is in the order of the day and is a goal whose implementation is desired by several entities. In this sense, several theories have arisen to measure the quality of life, among which we highlight the bottom-up spillover theory, once it is the most used (Diener, 1984; Diener, Suh, Lucas and Smith, 1999; Sirgy (2002) and Sirgy and Lee, 2006). To improve their quality of life, individuals choose to wellness tourism, where places like spas and other physical, spiritual and mental rehabilitation centers promote rest, relaxation, peace of mind and various treatments that meet what individuals yearn for. This trend in the demand for wellness tourism products and services has contributed to the growing demand for tourism activity in general and, especially, for the increase of revenues in this sector.